PENGALAMAN PERAWAT MELAKUKAN LATIHAN AKTIFITAS FISIK PADA PASIEN CONGESTIVE HEART FAILURE - Deni Susyanti; Mompang Tua Parlagutan; Muchti Yuda Pratama (Jurnal Riset Hesti Medan, 2018)
People with congestive heart failure (CHF) need a comprehensive rehabilitative program to restore physical abilities post-attacks and prevent re-attacks. Physical exercise in congestive heart failure (CHF) patients is aimed at optimizing the physical capacity of the body, providing counseling to patients and families in preventing worsening and helping patients to return to physical activity as before congestive heart failure (CHF). This study aims to explore in depth the experience of nurses doing physical exercise exercises in congetive heart failure patients. The research design used is descriptive phenomenology. Participants in this study amounted to 6 participants selected by purposive sampling technique. The data collected were in-depth interviews completed with field notes and then made in verbatim and analyzed using Colaizzi's approach. The research results found four themes, namely: the implementation of physical exercise exercise congestive heart failure patient is not optimal; increased knowledge of nurses and patients; the need for support from the hospital; and expectations for the exercise of physical activity. The results showed that things that could affect physical exercise activity in congestive heart failure patients were standard operating procedures, nurse knowledge, hospital support; and expectations for the exercise of physical activity. This study provides an understanding of the nurse's understanding of physical activity exercises so that nurses are able to provide appropriate nursing care.Keywords: experience, physical activity exercise, congetive heart failure